Beyond the ventilator - cardiovascular management in SARS-CoV-2 infection - Amy L Kloosterboer; Melissa A Vogelsong; Jessica L Brodt (Indian Journal of Respiratory Care, 2021)
The novel corona virus, severe acute respiratory syndrome coronavirus 2 has spread worldwide since late 2019, with clinical manifestations of coronavirus disease 2019 (COVID-19) ranging from asymptomatic to respiratory impairment to multiorgan dysfunction with life-threatening cardiovascular complications. The mechanism of cardiovascular involvement is likely multifactorial, hypothesized to include direct myocardial injury, secondary injury due to the inflammatory response, and macro- and microthrombotic complications due to hypercoagulability. Acute cor pulmonale and pulmonary embolism are cardiovascular causes of serious morbidity and mortality, and myocarditis and Takotsubo syndrome have also been reported. It is not clear if arrhythmias represent a primary viral effect or a secondary effect of disease severity, though certain pharmacotherapies such as hydroxychloroquine may increase this risk. Point-of-care ultrasound and echocardiography are important tools for the screening and monitoring of these potential complications. Cardiovascular decompensation must be managed supportively with the escalation of vasoactive support, inhaled vasodilators, and consideration of mechanical circulatory support. Many questions remain and ongoing study is required to optimize care of the patient with cardiovascular complications of COVID.19.